Lead-free MnTe mid-temperature thermoelectric materials: facile synthesis, p-type doping and transport properties. Issue 15 (4th April 2018) - Dong, Jinfeng; Wu, Chao-Feng; Pei, Jun; Sun, Fu-Hua; Pan, Yu; Zhang, Bo-Ping; Tang, Huaichao; Li, Jing-Feng
Abstract : This work reveals the effectiveness of sodium doping in MnTe as a thermoelectric material fabricated by a facile method. Abstract : MnTe has been found to exhibit good thermoelectric properties at medium temperature recently, but the electrical transport properties, especially the interaction between magnetism and carriers, are still not fully understood and the synthesis process reported is mainly composed of melting. Herein, we present a facile method combining mechanical alloying (MA) and spark plasma sintering (SPS) to fabricate high purity MnTe. Carrier concentration is well tuned by sodium doping, resulting in a high power factor over 900 μW m −1 K −2 and a maximum ZT value exceeding 1.0 at 873 K. The electrical transport properties are analyzed by the single parabolic band model. Additionally, different electrical transport properties induced by the magnetic transformation were discussed and clarified by first-principles calculation, including the increase of carrier concentration, decrease of mobility and enhancement of the density-of-state (DOS) effective mass. The high thermoelectric performance reveals the potential of MnTe as a promising candidate for medium-temperature thermoelectric materials.